Mongolia : 2012 Article IV Consultation and Third Post-Program Monitoring. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Mongolia has made impressive progress in developing its economy over the past ten years. Medium-term prospects are promising as mining output is projected to expand by more than 20 percent per annum, on average, over the next five years. However, the prospects for sustained, rapid and inclusive non-mineral growth depend on the implementation of the stability-oriented fiscal framework that has been adopted in the aftermath of the 2008/09 balance of payments (BOP) crisis. This framework was designed to dampen volatility, mitigate risks to economic and financial stability, and strengthen long-term natural resource management. The expansionary fiscal policy of the past year is causing double-digit inflation and BOP pressures. Public spending needs to be reined in, in order not to risk undermining stability and growth prospects, and in view of Mongolia's vulnerability to a downturn in commodities exports.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet